American Museum of Natural History Research Library 2014
DOI: 10.5531/sd.sp.7
|View full text |Cite
|
Sign up to set email alerts
|

High resolution images for 'A systematic review of Sulawesi Bunomys (Muridae, Murinae) with the description of two new species. (Bulletin of the American Museum of Natural History, no. 392)'

Abstract: Submission procedures can be found at http://research.amnh.org/scipubs On the cover: Dense, long, and silky-soft fur, brownishgray upperparts, grayish-white underparts, gray ears, white feet, and a bicolored tail characterize Bunomys penitus, one of eight documented species of Bunomys, all endemic to forested landscapes on the Indonesian island of Sulawesi. Nocturnal and terrestrial, B. penitus lives only in mountainforests where the ambience is cool and wet, the trees and ground covered with thick moss and ep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 30 publications
(55 reference statements)
0
1
0
2
Order By: Relevance
“…R. xanthurus is only found from northeastern Sulawesi (Musser and Carleton 2005). B. fratrorum found in northeast region of the northern peninsula of Sulawesi (Musser and Carleton 2005;Musser 2014). Recent studies have found it also recorded in the western part of the northern peninsula (Handika et al 2021).…”
Section: Species Of White-tailed Rats Hunted and Tradedmentioning
confidence: 99%
“…R. xanthurus is only found from northeastern Sulawesi (Musser and Carleton 2005). B. fratrorum found in northeast region of the northern peninsula of Sulawesi (Musser and Carleton 2005;Musser 2014). Recent studies have found it also recorded in the western part of the northern peninsula (Handika et al 2021).…”
Section: Species Of White-tailed Rats Hunted and Tradedmentioning
confidence: 99%
“…persebaran dari tikus menjadikannya sebagai salah satu reservoir penyakit. Penyakit Bunomys adalah salah satu genus tikus endemik di Sulawesi dan mempunyai habitat di daerah bukit berhutan, gunung dan lembah pegunungan (Musser 2014). Genus ini sampai saat ini mempunyai delapan jenis.…”
unclassified
“…Salah satu daerah yang dihuni tikus tersebut adalah Pegunungan Mekongga yang terletak di Sulawesi Tenggara. (Musser 2014;Grant et al 2003).…”
unclassified